Composition portfolio - Musambasi, Richie Andile (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
Indigenous Zimbabwean music is complex in its make up and reveals spiritual beliefs, modes of expression, communication patterns, and forms of entertainment. The goal of this composition portfolio is to create pieces that are imbued with the spirit of indigenous Zimbabwean music making as passed on from father to son. The pieces composed include thorough-composed (pre-determined) solo and ensemble frameworks using mostly marimbas based largely on Shona scales and tuning, but also adding mbira, hosho and djembe. All of this is presented within complex structural manipulations that include African and some Western elements of formal music structure. The compositions feature two interlocking parts, known as kushaura and kutsinhira (call and respond), which are traditionally played in a simultaneous manner by two or more musicians. In this portfolio, these voices are spread across a range of players where the interplay between the parts produces complex polyphonic and polyrhythmic musical relationships. The compositions explore modal changes which add excitement, variety and an extra layer of complexity to the pieces. The final artefact is presented as a multimedia submission recorded as a documentary in real time, which is a representation of the embodied making of the music, central to this project. As music was passed down through folk tales, religious gatherings, rock paintings and sources of art, the narration is the key element in expressing that knowledge dissemination is not only text bound, but also embodied and orally shared.
Keywords: Composition (Music); Ethnoscience; Oral tradition; Traditional knowledge; Marimba; Music Zimbabwe